Genomic DNA levels of mutant alpha-synuclein correlate with non-motor symptoms in an A53T Parkinson's disease mouse model. (March 2018) - Wang, Weiwei; Song, Ning; Jia, Fengjv; Tang, Tingting; Bao, Weiqi; Zuo, Chuantao; Xie, Junxia; Jiang, Hong
Abstract: Alpha-synuclein plays a key role in the pathogenesis of Parkinson's disease (PD). A robust transgenic mouse model has been generated that overexpresses the mutant human A53T alpha-synuclein under the mouse prion protein gene promoter; these mice develop age-dependent motor deficits. Recently, compared to wild-type (WT) littermates, A53T alpha-synuclein mice were reported to display non-motor symptom deficits, e.g., anxiety-like and depressive-like behaviors, odor discrimination and detection impairments, and gastrointestinal dysfunction, at 6 months of age or older. However, the differences between heterozygous and homozygous mice in terms of non-motor symptoms and whether the genomic DNA levels of alpha-synuclein correlate with the symptoms have not yet been elucidated. In the present work, we used littermate WT and heterozygous and homozygous A53T mice that were characterized by a modified genotyping protocol and observed a unilateral decline in the dopamine transporter (DAT) distribution from 3 months to 12 months of age in homozygous mice. We evaluated non-motor symptoms by measuring colon motility, anxiety-like and depressive-like behaviors, and motor coordination. The results showed that homozygous A53T mice exhibited earlier abnormal non-motor symptoms compared to their heterozygous littermates. The severity of impaired colon motility as well as anxiety-like and depressive-like behaviors were correlated with the genomic DNA levels of A53T mutant alpha-synuclein. More noticeable, motor coordination aberrances were also observed in homozygous A53T mice. This study provides direct evidence that the genomic DNA levels of mutant alpha-synuclein correlate with non-motor symptoms in an A53T mouse model, indicating that the genomic DNA levels of mutant alpha-synuclein should be tightly manipulated in PD model studies. Highlights: DAT distributions declined early in 3 months A53T homozygous mice. Both the nonmotor and motor symptoms came out earlier in homozygous mice than heterozygous mice. Nonmotor symptoms correlated with genomic DNA levels of mutant α-synuclein in A53T mice.